Penerapan Prinsip-Prinsip Manajemen Dakwah dalam Pembentukan Karakter Anak Panti Asuhan An-Nur - Meli Safitri; Nurhanifah (Universitas Sarjanawiyata Tamansiswa, 2025)
The implementation of the character development program at the An-Nur Orphanage faces several challenges, primarily due to the absence of structured management. This study aims to analyze the application of da'wah management principles in shaping the character of children at the orphanage. Using a qualitative descriptive method with a phenomenological approach, the study involved two key informants: the Head of the Orphanage and an Educator. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model. Findings reveal that applying da'wah management principles significantly supports character formation, particularly in fostering responsibility, discipline, cooperation, and understanding of Islamic values. Structured task division and regular religious activities contribute positively to the children's moral and social development. However, the study also identifies several barriers, including limited resources, insufficient caregiver training, and minimal community engagement. Enhancing the program’s effectiveness requires improvements in training, increased community involvement, and better resource management. This study offers valuable insights for orphanage administrators and the broader community in optimizing da'wah-based management to nurture strong, faith-based character in children.